Electrocardiographic Pattern in Children suffering from Diphtheria during 1973 at Dr. Cipto Mangunkusumo Hospital, Jakarta - Maemunah Affandi; Bambang Madiyono; Otty W. Sonityo; Purwana K. G. (Indonesian Pediatric Society, 1976)
ECG abnormalities were found in 39 (45.3%) out of 86 diphtheria cases; 29 cases (33.6%) had significant myocardial involvement. Myocardial involvement comprised minor changes in 24 cases and major changes in 5 cases. Twenty two cases of myocardial involvement occurred in the first week of hospitalization, while 7 cases occurred after the first week of hospitalization. The ECG abnormalities of the 29 cases disappeared within 1 to 2 weeks or after 3 weeks. Minor changes have a good prognosis, while major changes, especially an AV block, have a poor prognosis.